Case Report: Pemphigus following COVID-19 mRNA vaccination: two cases achieving long-term remission without relapse - Fukunaga, Yuri; Saito-Sasaki, Natsuko; Ohta, Eri; Sawada, Yu (Frontiers in Immunology, 2026)
Autoimmune blistering diseases (AIBDs) are mediated by autoantibodies targeting structural proteins of the epidermis or dermo-epidermal junction. Since the introduction of COVID-19 mRNA vaccines, isolated cases of pemphigus temporally associated with vaccination have been described, although causal relationships remain uncertain. We report two patients who developed pemphigus following COVID-19 mRNA vaccination and showed an exceptionally favorable clinical course. A 66-year-old man developed pemphigus foliaceus one week after his second vaccine dose, and a 45-year-old woman developed pemphigus vulgaris two months after her second dose. Both patients responded promptly to corticosteroid therapy, with normalization of autoantibody titers and achievement of long-term complete remission lasting over two years without relapse or maintenance therapy. These outcomes stand in contrast to sporadic pemphigus, which usually follows a chronic relapsing course, and suggest that vaccine-related pemphigus may, in rare instances, represent a transient and self-limited immune dysregulation. Such cases are exceptional and should not discourage COVID-19 vaccination.